Enhanced removal of Cr(VI) from aqueous solutions using poly(pyrrole)-g-poly(acrylic acid-co- acrylamide)/Fe3O4 magnetic hydrogel nanocomposite adsorbent - Hosseinzadeh, Hossein (Array, 2019)
In the present work, the structural characterization and chromium adsorption behavior of a novel poly(pyrrole)-based magnetic hydrogel nanocomposite (MHN) is reported. This product was prepared using free-radical copolymerization of pyrrole (Py), acrylic acid (AA) and acrylamide (AM) monomers, and subsequent in situ synthesis of magnetic Fe3O4 nanoparticles. The structure of MHNs was then characterized by FTIR, SEM, TEM, XRD, UV-Vis and VSM techniques, and a mechanism for the preparation of MHNs is also proposed. The maximum Cr(VI) adsorption capacity (208 mg g–1) was achieved under the optimum conditions that were found to be: AA = 0.25 mol L–1, AM = 1.2 mol L–1, agitation time = 90 min, solution pH = 1.0, ion concentration = 100 mg L–1, adsorbent dose = 50 mg, and temperature = 65 °C. Further, the calculated values of the thermodynamic parameters (ΔH° = 31.33kJ mol–1, ΔS° = 105.67 J K–1 mol–1, ΔG° = –61.33 kJ mol–1) revealed that ion adsorption is a spontaneous and endothermic process. In general, the results indicated that the synthesized MHNs with specific properties can be used in wastewater treatment applications.